PENGARUH MOTIVASI KERJA, KOMUNIKASI DAN KOMITMEN TERHADAP PROFESIONALISME GURU IPA SMP DI RAYON SABATU KABUPATEN PARIGI MOUTONG (Studi Kasus pada Rayon Sausu, Balinggi dan Torue) - Ali, Ali (JSTT, 2014)
The objectives of this research were to find out the information and determine the influence of teachersâ€™ working motivation, comminication and commitment toward science teachersâ€™ profesionalism in Sabatu Region I Parigi Moutong Regency. This was a quantitative research with survey method. The poulation was the science teachers of SMP in Parigi Moutong Regency Sabatu Region (Sausu, Balinggi and Torue) academic year 2011/2012. The sample was 30 Science teachers. The techique of data collection used questionnaire. The researdh results show that: there was a significart influence of motivation toward Science teacherâ€™ professionalism(Ï=0.000) wich was 67.0%; there was a significant influence of teachersâ€™ comunication toward Science teachersâ€™ professionalism (Ï=0.000) was 55.8%; there was a significant influence of teachersâ€™ commitment toward Science teachersâ€™ professionalism (Ï=0.000) was 68.4%; and there was a significant influence of teachersâ€™ working motivation, teachersâ€™ communication and teachersâ€™ commitment simultaneously toward Science teachersâ€™ profesionalism which was 71.5%.